2004
DOI: 10.1128/jvi.78.3.1503-1512.2004
|View full text |Cite
|
Sign up to set email alerts
|

Both the PPPY and PTAP Motifs Are Involved in Human T-Cell Leukemia Virus Type 1 Particle Release

Abstract: In retroviruses, the late (L) domain has been defined as a conserved motif in the Gag polyprotein precursor that, when mutated, leads to the emergence of virus particles that fail to pinch off from the plasma membrane. These domains have been observed to contain the PPXY, PTAP, or YXXL motifs. The deltaretroviruses, which include bovine leukemia virus (BLV) and human T-cell leukemia virus type 1 (HTLV-1) and HTLV-2, have a conserved PPPY motif in the C-terminal region of the matrix (MA) domain of Gag, while HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 49 publications
6
58
2
Order By: Relevance
“…In agreement with other studies that utilized mini-Gag constructs, we observed that the PPXY motif can greatly stimulate the release of mini-Gag particles, which is in marked contrast to its apparent inability to stimulate the release of full-length Gag (41) but consistent with results reported for HTLV, where the PPXY motif has been shown to greatly increase particle release (8,24,74). We also observed a positive correlation between the extent of Gag ubiquitination and particle release in the context of a mini-Gag construct carrying the late domains of HTLV and Ebola virus, as reported earlier (41,67).…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with other studies that utilized mini-Gag constructs, we observed that the PPXY motif can greatly stimulate the release of mini-Gag particles, which is in marked contrast to its apparent inability to stimulate the release of full-length Gag (41) but consistent with results reported for HTLV, where the PPXY motif has been shown to greatly increase particle release (8,24,74). We also observed a positive correlation between the extent of Gag ubiquitination and particle release in the context of a mini-Gag construct carrying the late domains of HTLV and Ebola virus, as reported earlier (41,67).…”
Section: Discussionsupporting
confidence: 81%
“…In the context of both intact PFV and in a PFV-based vector system, mutation of each individual candidate L domain had no effect on levels of Gag protein synthesis, but resulted in a significant reduction in the yield of virus particles. Mutation of either the PSAP or PPPI domain reduced viral titer by 2.5-to 10-fold, an effect similar in magnitude to that observed upon mutation of the L domains of other retroviruses (5,15,16,45,47). L domains frequently occur in combination and bind separate cofactors.…”
Section: Discussionmentioning
confidence: 62%
“…In HTLV-1, there are two conserved late domain motifs, PPPY and PTAP that are found in the matrix region (161,188). Specifically, the late domains of HTLV-1 Gag have recently been found to recruit ubiquitin ligases Nedd4 and Tsg101, a protein of the ESCRT-1 complex, to facilitate the budding process (14).…”
Section: Gagmentioning
confidence: 99%